Phosphatidylinositol-3-OH kinase and nutrient-sensing mTOR pathways control T lymphocyte trafficking - FINLAY, DAVID (Nature, 2008)
Phosphatidylinositol-3-OH kinase (PI(3)K) and the nutrient sensor mTOR are evolutionarily conserved regulators of cell metabolism. Here we show that PI(3)K and mTOR determined the repertoire of adhesion and chemokine receptors expressed by T lymphocytes. The key lymph node-homing receptors CD62L (L-selectin) and CCR7 were highly expressed on naive T lymphocytes but were downregulated after immune activation. CD62L downregulation occurred through ectodomain proteolysis and suppression of gene transcription. The p110delta subunit of PI(3)K controlled CD62L proteolysis through mitogen-activated protein kinases, whereas control of CD62L transcription by p110delta was mediated by mTOR through regulation of the transcription factor KLF2. PI(3)K-mTOR nutrient-sensing pathways also determined expression of the chemokine receptor CCR7 and regulated lymphocyte trafficking in vivo. Hence, lymphocytes use PI(3)K and mTOR to match metabolism and trafficking.
PUBLISHED
Keywords: Immunology; CD62L